The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.23919/saiee.2018.8531951
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Ethical Nudging in Password Authentication

Abstract: This research investigates the Electromagnetic (EM) side channel leakage of a Raspberry Pi 2 B+. An evaluation is performed on the EM leakage as the device executes the AES-128 cryptographic algorithm contained in the libcrypto++ library in a threaded environment. Four multi-threaded implementations are evaluated. These implementations are Portable Operating System Interface Threads, C++11 threads, Threading Building Blocks, and OpenMP threads. It is demonstrated that the various thread techniques have distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In another online study following a 2 × 2 × 4-within and between subject design, Zimmermann and Renaud ( 2021 ) found that hybrid nudges, i.e., nudges that provide additional information, lead to better security decisions, including password choice, compared to providing mere information. Renaud and Zimmermann ( 2018 a) further provided guidelines for conducting nudge experiments, particularly in the password authentication context. Other studies explored innovative authentication methods, e.g., relying on 3D-printed items for two-factor authentication (Marky et al.…”
Section: Usable Security and Privacymentioning
confidence: 99%
“…In another online study following a 2 × 2 × 4-within and between subject design, Zimmermann and Renaud ( 2021 ) found that hybrid nudges, i.e., nudges that provide additional information, lead to better security decisions, including password choice, compared to providing mere information. Renaud and Zimmermann ( 2018 a) further provided guidelines for conducting nudge experiments, particularly in the password authentication context. Other studies explored innovative authentication methods, e.g., relying on 3D-printed items for two-factor authentication (Marky et al.…”
Section: Usable Security and Privacymentioning
confidence: 99%
“…Researchers in the security and privacy area have been exploring ways to nudge users to better their security decisions (Renaud and Zimmermann, 2018;Cooper et al, 2020). For instance, Peer et al (2020) developed a personalized approach that analyzed individual differences in decision-making to encourage users to choose stronger and safer passwords.…”
Section: Literature Review 21 Nudges In Cybersecuritymentioning
confidence: 99%